2009
DOI: 10.1101/gad.543509
|View full text |Cite
|
Sign up to set email alerts
|

Increased telomere fragility and fusions resulting from TRF1 deficiency lead to degenerative pathologies and increased cancer in mice

Abstract: The telomere repeat-binding factor 1 (TERF1, referred to hereafter as TRF1) is a component of mammalian telomeres whose role in telomere biology and disease has remained elusive. Here, we report on cells and mice conditionally deleted for TRF1. TRF1-deleted mouse embryonic fibroblasts (MEFs) show rapid induction of senescence, which is concomitant with abundant telomeric g-H2AX foci and activation of the ATM/ATR downstream checkpoint kinases CHK1 and CHK2. DNA damage foci are rescued by both ATM and ATM/ATR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
531
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(572 citation statements)
references
References 60 publications
34
531
1
6
Order By: Relevance
“…These features pose challenges to replication machinery, and replication forks are vulnerable to stalling at telomeric tracts [23,24]. This is validated by recent reports demonstrating that telomeres resemble common fragile sites and efficient replication of telomeric DNA requires assistance from telomerebinding proteins as well as associated factors [25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 48%
“…These features pose challenges to replication machinery, and replication forks are vulnerable to stalling at telomeric tracts [23,24]. This is validated by recent reports demonstrating that telomeres resemble common fragile sites and efficient replication of telomeric DNA requires assistance from telomerebinding proteins as well as associated factors [25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 48%
“…Ft1 kof/kof mice displayed multiple traits that have been previously observed in several progeroid models (Table S2). We found that Ft1 mutant mice have reduced body weight, fertility defects, and reduced lifespan, as previously observed in models of laminopathies (Bergo et al., 2002; Osorio, Navarro, et al., 2011) and telomeropathies (Martínez et al., 2009). In addition, the growth defects of Ft1 kof/kof mice were exacerbated with aging, suggesting that the effects of Ft1 mutations intercept the normal aging‐induced degeneration pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the growth defects of Ft1 kof/kof mice were exacerbated with aging, suggesting that the effects of Ft1 mutations intercept the normal aging‐induced degeneration pathways. Ft1 kof/kof mice also displayed skin and bone defects, which were previously observed in lamin mutant mice (Bergo et al., 2002; Mounkes et al., 2003; Osorio, Navarro, et al., 2011), in Tert ko animals (Rudolph et al., 1999), and in mice with reduced Trf1 expression (Martínez et al., 2009). Skeletal alterations and lipodystrophy have been imputed to failures in the proliferation of mesenchymal stem cell progenitors, which are sensitive to lamin mutations and senescence (Scaffidi & Misteli, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Anaphase bridges are found among cells exhibiting impaired telomere homeostasis [39][40][41][42] and defective DNA DSB repair. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] RINT1 is known to be involved in both pathways through interaction with p130 15 or Rad50. 14 The structure of chromosome fusion in the Rint1-deficient cells supports the hypothesis of defective DSB repair (Figures 4c and d).…”
Section: Discussionmentioning
confidence: 99%